2004
DOI: 10.1016/j.ydbio.2004.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses in the hemipteran Oncopeltus fasciatus reveal conserved and derived aspects of appendage patterning in insects

Abstract: The conservation of expression of appendage patterning genes, particularly Distal-less, has been shown in a wide taxonomic sampling of animals. However, the functional significance of this expression has been tested in only a few organisms. Here we report functional analyses of orthologues of the genes Distal-less, dachshund, and homothorax in the appendages of the milkweed bug Oncopeltus fasciatus (Hemiptera). This hemimetabolous insect has typical legs but highly derived mouthparts. Distal-less, dachshund, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
91
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 42 publications
14
91
0
Order By: Relevance
“…Among hemimetabolous insects, in the cricket G. bimaculatus, parental RNAi-mediated knockdown of hth resulted in similar transformation of all cephalic appendages towards leg identity in some embryos, and comparable fusion of adjacent segments in stronger phenotypes [26]. In parental RNAi experiments with the milkweed bug O. fasciatus, weaker hth phenotypes consisted of distal labium (second maxilla)-to-leg transformations, and truncation of antennae [24]. The similar range of phenotypes observed upon knockdown of hth orthologues in multiple insects and the chelicerate exemplar P. opilio suggests evolutionary conservation of hth function in proximo-distal patterning and cephalic appendage specification over 550 million years of arthropod evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Among hemimetabolous insects, in the cricket G. bimaculatus, parental RNAi-mediated knockdown of hth resulted in similar transformation of all cephalic appendages towards leg identity in some embryos, and comparable fusion of adjacent segments in stronger phenotypes [26]. In parental RNAi experiments with the milkweed bug O. fasciatus, weaker hth phenotypes consisted of distal labium (second maxilla)-to-leg transformations, and truncation of antennae [24]. The similar range of phenotypes observed upon knockdown of hth orthologues in multiple insects and the chelicerate exemplar P. opilio suggests evolutionary conservation of hth function in proximo-distal patterning and cephalic appendage specification over 550 million years of arthropod evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the recent expression and functional analyses on Dll's role in mandible development collectively suggest that Dll does not play a significant role in the mandibular development of insects (Panganiban et al 1994, Popadic et al 1998, Beermann et al 2001, Angelini & Kaufman 2004, Angelini & Kaufman 2005, Simonnet & Moczek 2011, Coulcher & Telford 2013, and our a priori assumption was that Dll would not be not expressed in stag beetle mandibles. However, it is known that Dll has been independently co-opted during the development of novel traits, especially epidermal outgrowths in insects (Panganiban et al 1994, Moczek & Nagy 2005, Moczek & Rose 2009, Toga et al 2012, raising the possibility that distal patterning, including Dll expression, might have been restored in the evolution of extreme mandible size in these beetles.…”
Section: Distal-less (Dll)mentioning
confidence: 86%
“…It has been suggested that patterns of Hox gene expression are correlated with the evolution of novel mouthpart morphologies [37][38][39]. In Protura, Collembola and Diplura, Hox gene expression in developing mouthparts has not been studied yet; therefore, the influence of these regulatory mechanisms on the general principle is unclear.…”
Section: (C) the Evolution Of Structural Mouthpart Interactions In Inmentioning
confidence: 99%